2005
DOI: 10.1111/j.1572-0241.2005.41649.x
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Endoscopy versus Standard Tests in Influencing Management of Obscure Digestive Bleeding: Results from a German Multicenter Trial

Abstract: CE helps with management decisions and can replace other more complex and risky standard tests. Nevertheless, clinical parameters are equally important for predicting further bleeding and should also be used to decide on further management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 23 publications
4
32
1
7
Order By: Relevance
“…The diagnostic yield of CE in OGIB in the present study (36%) was lower than those reported in western literatures (42%-71%) [6,7,[10][11][12][13][14][15][16] and those reported in metaanalyses (61%-63%) [3,4] . There are many possible reasons.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The diagnostic yield of CE in OGIB in the present study (36%) was lower than those reported in western literatures (42%-71%) [6,7,[10][11][12][13][14][15][16] and those reported in metaanalyses (61%-63%) [3,4] . There are many possible reasons.…”
Section: Discussioncontrasting
confidence: 83%
“…The very low rebleeding rate in patients with positive CE results (together with appropriate management according to the CE findings) is found to be lower than those reported from the West [6,7,[10][11][12][13][14][15][16] . The low rebleeding in our study could be due to the spontaneously improved nature of the disease (i.e., NSAID-induced ulcers) and the ability to provide specific treatments, i.e., surgery for small bowel tumors, which were also prevalent in this study.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This implies that a normal examination may not always expedite a diagnosis; however, it allows the physician to quit a certain line of investigations and advocate an expectant approach. One of the first studies trying to assess the cumulative re-bleeding rate of OGIB was published in 2005 by Neu et al (18). In this prospective, multicenter study, re-bleeding occurred more frequently in patients with positive than negative VCE (44.7% vs. 22.2%) after 13-month follow-up period.…”
Section: Re-bleeding Rate After Index Vce Small Bowel Examinationmentioning
confidence: 97%
“…In particular, depletion of the two silver oxide batteries used in current devices may prevent complete imaging of the small intestine if the pill remains in the stomach for too long. The problem becomes most apparent by the inability to view the cecum (the marker of a complete examination) in 10%-15% of CE examinations of the small bowel (Neu et al,2005;Triester et al,2006).This will eventually be overcome by using power transfer methods from outside the body. In the short term, this problem can partly be solved by using more efficient power management algorithms that enable an 11 h recording time.…”
Section: Next Generation Capsule Endoscopymentioning
confidence: 99%